Opuntia ficus-indica Extract as Green Corrosion Inhibitor for Carbon Steel in 1 M HCl Solution - J. P. Flores-De los Ríos; M. Sánchez-Carrillo; C. G. Nava-Dino; J. G. Chacón-Nava; J. G. González-Rodríguez; E. Huape-Padilla; M. A. Neri-Flores; A. Martínez-Villafañe (Journal of Spectroscopy)
The effect of Opuntia ficus-indica (Nopal) as green corrosion inhibitor for carbon steel in 1 M HCl solution has been investigated by using weight loss tests, potentiodynamic polarization curves, and electrochemical impedance spectroscopy measurements. Also, scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR) analysis were performed. The inhibitor concentrations used ranged from 0 to 300 ppm at 25, 40, and 60°C. Results indicated the inhibition efficiency increases with increasing extract concentration and decreases with the temperature, and the inhibitor acted as a cathodic-type inhibitor which is physically absorbed onto the steel surface. In fact, the adsorption of the inhibitor on the steel surface follows the Langmuir adsorption isotherm, indicating monolayer adsorption. The presence of heteroatoms such as C, N, and O and OH groups were responsible for the corrosion inhibition.